2023
DOI: 10.1177/1934578x221148896
|View full text |Cite
|
Sign up to set email alerts
|

Vanillic Acid Alleviates Right Ventricular Function in Rats With MCT-Induced Pulmonary Arterial Hypertension

Abstract: This study examined the molecular processes behind the effects of vanillic acid (VA) on right ventricular (RV) hypertrophy and function in rats with monocrotaline (MCT)-induced pulmonary arterial hypertension (PAH). There were 40 male Sprague‒Dawley (SD) rats that were separated into 4 groups: Control, PAH, MCT + VA (50 mg/kg/d), and MCT + VA (100 mg/kg/d). Male SD rats were injected with MCT once under the skin to create the PAH model (40 mg/kg). RV morphological properties were evaluated using Masson and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…A previous study found that VA could alleviate pulmonary vascular remodeling by enhancing NO signaling pathways in MCT‐induced PAH rat (Wang et al, 2022). We also found that VA had a significant intervention effect on right ventricular remodeling and right ventricular function in MCT‐induced PAH rat (J. Chen et al, 2023). However, its efficacy was not shown to be dose dependent and we wondered whether the bioavailability of VA in PAH rats had changed.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…A previous study found that VA could alleviate pulmonary vascular remodeling by enhancing NO signaling pathways in MCT‐induced PAH rat (Wang et al, 2022). We also found that VA had a significant intervention effect on right ventricular remodeling and right ventricular function in MCT‐induced PAH rat (J. Chen et al, 2023). However, its efficacy was not shown to be dose dependent and we wondered whether the bioavailability of VA in PAH rats had changed.…”
Section: Introductionmentioning
confidence: 73%
“…We also found that VA had a significant intervention effect on right ventricular remodeling and right ventricular function in MCT-induced PAH rat (J. Chen et al, 2023). However, its efficacy was not shown to be dose dependent and we wondered whether the bioavailability of VA in PAH rats had changed.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is necessary to fully understand the mechanisms by which probiotics influence cardiac fibrosis and their overall effects on the gut microbiome in the context of different disease conditions. Piperine Alkaloids nigrum) [171,202] Ginsenoside Saponins Ginseng root [173] Astragaloside IV Saponins Astragalus membranaceus [172] Coumarins Coumarins tonka bean, cassia bark [174] Stilbenes Stilbenes grapes, peanuts, and berries [150,177] Caffeic acid Phenolic acids apples and red wine [178,179] Chlorogenic acid Phenolic acids Coffee [180,181] Vanillic acid Phenolic acids vanilla beans [182] Anthocyanins Anthocyanins red and purple berries, grapes, apples, plums, cabbage, or foods containing high levels of natural colorants [183] Tannins Tannins plant-based foods and beverages, such as tea, coffee, and wine [184] tonka bean, cassia bark [174] Stilbenes Stilbenes…”
Section: Probioticsmentioning
confidence: 99%
“…Astragaloside IV Saponins Astragalus membranaceus [172] Coumarins Coumarins tonka bean, cassia bark [174] Stilbenes Stilbenes grapes, peanuts, and berries [150,177] Caffeic acid Phenolic acids apples and red wine [178,179] Chlorogenic acid Phenolic acids Coffee [180,181] Vanillic acid Phenolic acids vanilla beans [182] Anthocyanins Anthocyanins red and purple berries, grapes, apples, plums, cabbage, or foods containing high levels of natural colorants [183] Tannins Tannins plant-based foods and beverages, such as tea, coffee, and wine [184] red and purple berries, grapes, apples, plums, cabbage, or foods containing high levels of natural colorants [183] Tannins Tannins…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation